Peningkatan Kualitas Manajemen Sumber Daya Manusia Pada Perbankan Syariah - Niyar Andina; Amanda Dwiyanti (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
The aim of this research is to describe how to improve the quality of sharia banking human resources. The sharia banking industry faces various challenges, including human resource problems. Therefore, effective management is very important to improve the HR standards of Sharia Banks. This writing uses a qualitative analysis strategy known as a literature study or literature review, where the author uses research taken from various articles on human resource management to find relevant discussions.From these findings, it can be inferred that in order to raise the standard of human resource management in sharia banking, it is imperative to create training and educational programs about the human resources required in sharia banking as well as to implement certification programs. This is because it is challenging for an individual to compete in the globalized world without a certificate proving one's expertise in the field.